Selection of different-sized prey by sharp-shinned hawks (Accipiter striatus) and northern goshawks (A. gentilis) - Meader, Gary Alan (My University, 1988)
The primary objective of this study was to experimentally test the hypothesis that a positive correlation exists between weight of accipters and the weight of their prey. Sharp-shinned hawks (Accipiter striatus) and northern goshawks (A. gentilis) were selected for the study due to their abundance during migration, ease of trappings, and differences in weight.
Keywords: Predation (Biology); Goshawk; Sharp-shinned hawk